The Sustain of the Leadership Methodology in Higher Education - Balla, Tibor (International Journal of Engineering and Management Sciences, 2016)
Higher education institutions have to follow the changes of current higher education and market oriented atmosphere. All these changes have to be measured and probably reacted to. Leaders of higher education instutions should have personal skills, which can contribute to the efficiency therefore they can motivate their colleagues. The aim of this study is to unfold the most effective measuring model to determine the leadership competencies, behaviours, properties, which can contribute to the successful operation and to the subsistence of experienced competition in higher education.